Incidental Parathyroid Disease during Thyroid Surgery: Should We Remove Them?. (4th April 2011) - Helme, S.; Lulsegged, A.; Sinha, P.
Abstract : Aim . Despite an incidence of parathyroid "incidentalomas" of 0.2%–4.5%, only approximately 135 cases have been reported in the literature. We present eight patients in whom an incidental abnormal parathyroid gland was found during routine thyroid surgery. We have reviewed the literature and postulate whether these glands could represent further evidence of a preclinical stage of primary hyperparathyroidism. Methods . A retrospective analysis of all 236 thyroid operations performed by a single surgeon was performed to identify patients in whom abnormal parathyroid tissue was removed at surgery. Results . 8/236 patients (3.39%) had a single macroscopically abnormal parathyroid gland removed and sent for analysis. Seven patients were found to have histological evidence of a parathyroid adenoma or hyperplasia. None of the patients had abnormal serum calcium detected preoperatively. Postoperatively, four patients had normal calcium, three had temporary hypocalcaemia and one refused followup. No patients had recurrent laryngeal nerve impairment. Conclusions . Despite the risk of removing a histologically normal gland, we believe that when parathyroid "incidentalomas" are found during surgery they should be excised and sent for histological analysis. We have found this to be a safe procedure with minimal morbidity to the patient. As the natural history of primary hyperparathyroidism is better understood, these glands found in normocalcaemic patients may in fact represent the early or preclinical phase of the disease. By removing them at the original operation, the patient is saved redo neck surgery with its high complication rate as or when clinically apparent primary hyperparthryoidism develops in the future.